MECHANISMS OF STRENGTHENING AND MAINTAINING THE HEALTH OF YOUNG PEOPLE, RAISING THEIR SPIRITUAL AND MORAL LEVEL - Ruziyeva Muhayo Erkinovna, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
Health is an invaluable asset not only of each person, but of the entire society. When we meet and say goodbye to close and dear people, we wish them good health, because this is the main condition and guarantee of a full and happy life. Health is not only the absence of disease or physical infirmity, but also complete physical, mental and social well-being. This article deals with the problems of strengthening and maintaining the health of young people, raising their spiritual and morel level.